Bottled water: Analysis of mycotoxins by LC–MS/MS. (1st June 2015) - Mata, A.T.; Ferreira, J.P.; Oliveira, B.R.; Batoréu, M.C.; Barreto Crespo, M.T.; Pereira, V.J.; Bronze, M.R.
Highlights: An analytical method comprising SPE procedure and LC–MS/MS analysis was validated. Trace analysis of mycotoxins was performed in commercially available bottled waters. Fungi and mycotoxins were detected in bottled water samples. The consumption of these waters does not represent a toxicological risk for an adult. Abstract: The presence of mycotoxins in food samples has been widely studied as well as its impact in human health, however, information about its distribution in the environment is scarce. An analytical method comprising a solid phase extraction procedure followed by liquid chromatography tandem mass spectrometry analysis was implemented and validated for the trace analysis of mycotoxins in drinking bottled waters. Limits of quantification achieved for the method were between 0.2 ng L −1 for aflatoxins and ochratoxin, and 2.0 ng L −1 for fumonisins and neosolaniol. The method was applied to real samples. Aflatoxin B2 was the most frequently detected mycotoxin in water samples, with a maximum concentration of 0.48 ± 0.05 ng L −1 followed by aflatoxin B1, aflatoxin G1 and ochratoxin A. The genera Cladosporium, Fusarium and Penicillium were the fungi more frequently detected. These results show that the consumption of these waters does not represent a toxicological risk for an adult.